HUBUNGAN KUALITAS SUMBER DAYA MANUSIA TERHADAP PELAYANAN PUBLIK DI KELURAHAN ADIPURO KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Eka Ubaya Taruna Rauf; Suhartina Suhartina (Jurnal Bisnis Darmajaya, 2022)
ABSTRACTIn Adipuro Village, Trimurjo District, Central Lampung Regency, this study aims to determine the relationship between the quality of human resources and public services. This study uses the method of observation, documentation, and questionnaires. Quantitative analysis using the Pruduct Moment Correlation formula and SPSS version 16.0 was used as the analysis method. A simple correlation analysis (r) between the correlation of the quality of human resources (X) to public services (Y) yields a relationship result of 0.527 or 52.7 percent between the quality of human resources in public services and computerized data processing using the SPSS version 16.0 program. This shows that there is a relationship between the quality of public services (Y) and human resources (X). Even though r is positive, the direction of the relationship is positive. This indicates that the expansion of public services in Adipuro Village, Trimurjo District, Central Lampung Regency, will be accompanied by a greater focus on the quality of human resources. The rest, on the other hand (100% –52.7% = 47.3%), can be explained or influenced by other factors not examined in this study. Keywords: Quality, of Human, Resources, Public, Service